BRAF G596R mutation in a slow-progressing melanoma - Gao L; Ma D (Dove Medical Press, 2015)
Ling Gao, Deqin Ma Department of Pathology, University of Iowa Hospitals and Clinics, Iowa City, IA, USA Abstract: More than 50% of melanomas harbor a single V600E point mutation in the kinase domain of the BRAF gene, resulting in constitutive activation of the MAP kinase pathway. The kinase loop in BRAF begins with Asp-Phe-Gly (DFG; codons 594–596). Mutations in this region are rare, and the effect on tumorigenesis or progression is unknown. We present a slow-progressing metastatic melanoma with a p.G596R (c.1786G>C) mutation in an 84-year-old female. This mutation has only been reported in two cases of melanoma in the current literature, with no clinical information available. Mutations in the DFG motif are considered low-activating through indirect binding and allosteric activation of the CRAF protein. Our patient has carried a clinical diagnosis of melanoma for over 25 years, suggesting that the G596R mutation may be associated with her indolent clinical course. It is unknown whether patients carrying this mutation will benefit from vemurafenib therapy. Our patient declined medical treatment. Keywords: melanoma, BRAF, V600E, G596R